2005
DOI: 10.2118/05-01-04
|View full text |Cite
|
Sign up to set email alerts
|

SAGD Wind-Down: Lab Test and Simulation

Abstract: As SAGD moves from pilot test to commercial operation, a number of issues need to be dealt with. These include diagnosing and solving operational problems and improving energy efficiency. One of the methods of improving energy efficiency is to prolong oil production after steam injection stops by using the energy remaining in place. The results of a laboratory experiment and corresponding numerical history matching are reported in this paper. The study showed that the hot chamber continued its expansion after … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 5 publications
1
7
0
1
Order By: Relevance
“…Zhao et al (2005) experimentally investigated a SAGP application during a wind down process, which indicated that 12.5% more original oil in place could be produced compared with SAGD. 222 All these results demonstrated that SAGP was a good modification to SAGD. NCG coinjection with steam could reduce heat loss after a chamber contacts with overburden.…”
Section: ■ Css Follow-up Processes and Simulationmentioning
confidence: 86%
See 1 more Smart Citation
“…Zhao et al (2005) experimentally investigated a SAGP application during a wind down process, which indicated that 12.5% more original oil in place could be produced compared with SAGD. 222 All these results demonstrated that SAGP was a good modification to SAGD. NCG coinjection with steam could reduce heat loss after a chamber contacts with overburden.…”
Section: ■ Css Follow-up Processes and Simulationmentioning
confidence: 86%
“…In SAGD, a steam chamber cannot penetrate a low permeability layer until the temperature in this layer reached steam temperature, while in SAGP gas fingers were easier to penetrate this layer, which demonstrated that SAGP could have a better performance in a reservoir with low perm layers than SAGD. Zhao et al (2005) experimentally investigated a SAGP application during a wind down process, which indicated that 12.5% more original oil in place could be produced compared with SAGD . All these results demonstrated that SAGP was a good modification to SAGD.…”
Section: Sagd Noncondensable Gas (Ncg) Coinjectionmentioning
confidence: 99%
“…Other sets of experiments to evaluate the wind-down process by injecting NCG after SAGD resulted in a recovery of 12.5%. 6 The temperature profile demonstrated that the hot chamber continued growing when the steam injection stopped due to the expansion/pressurization with NCG addition. In another study, two sets of experiments were conducted to evaluate the NCG distribution in the SAGD chamber when there was initial gas saturation: one at low pressure and one at high pressure.…”
Section: Introductionmentioning
confidence: 98%
“…This discrepancy in the literature is due to unknowns associated with reservoir rock and reservoir fluid interaction and high asphaltenic content of reservoir fluids (Kar et al, 2016). Both the liquid-gas relative permeabilities and relative permeability end point as a function of temperature are important simulation parameters for performance estimation of hot-water and steam injection processes, but most simulation studies ignore their importance and do not introduce those parameters into the model by assuming two-phase flow (Li and Horne, 2003;Zhao et al, 2005;Hascakir and Kovscek, 2010 ).…”
Section: Introductionmentioning
confidence: 99%